Effect of Elderly Exercises on Increasing Memory (Mini-Mental State Examination =MMSE) - Muhammad Arsyad Subu; Hafnah Rosita; Imam Waluyo; Dwi Ratna Sari Handayani (Syntax Idea)
The purpose of this study was to examine the effect of elderly exercise intervention on Memory (MMSE) in the elderly in Bogor Regency, West Java. Method by conducting interviews and observations with MMSE before intervention. The next step is to provide elderly exercise care to improve MMSE. The results of the difference in average MMSE scores were compared to see how far the effect of elderly exercise interventions on memory function. The minimum number of samples was determined by the test formula of the mean difference before and after the intervention with a total of 11 and to maintain the drop out the number of samples was 20 subjects. with dropout criteria, if they did not participate in the exercise 3 times during the intervention. Results: The overall mean ± the SD age range was 95% CI 64.4 ± 3.77 with a minimum age of 60 years and a maximum of 66 years with a CI of 95% (62.4 – 66.3). Where the average age of primary ± for men was 76.0 ± 2.82, the median age for women was 63.6 ± 3.75. The overall mean value of several cognitive components increased after the administration of elderly exercise so that there was a cognitive influence of the elderly where the cognitive value before the elderly exercise intervention was 22.00 ± 6.010 with a confidence level of 95% (95% CI) between 18.91 – 25.09 and the average cognitive value after the elderly exercise intervention was 26.53 ± 68.3 with a confidence level of 95% (95% CI) between 24.53 – 28.53. Conclusion: The conclusion of the intervention before and after elderly exercise on the effect of MMSE scores showed significant results before and after the elderly exercise intervention.